HUBUNGAN STRATEGIC COST MANAGEMENT PADA TRANSPORTASI ONLINE (RODA DUA) TERHADAP PEMBERDAYAAN EKONOMI MASYARAKAT (Studi Kasus Pada PT GO-JEK Indonesia) - Muzakkir, Nur Ain Pratiwi; Novita, Novita (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2016)
This research was aimed to determine the relationship of the application of strategic cost management (SCM) on a online transportation business (two wheels) towards community economic empowerment. To achieve these objectives, the research conducted on the driver's PT GO-JEK Indonesia as research samples. Data were collected through questionnaires distributed to 70 drivers as the research sample. Data were analyzed by using descriptive quantitative analysis of the nine indicators of variable SCM namely, cost leadership and differentiation, cost control, income level, efficient use of resources, the effectiveness of the process of providing the service, price, time, quality and function, relationship, as well as the brand and three indicators of community economic empowerment variables, namely, the conditions and standard of living, partnerships, ability to work and produce output. Based on the survey results and analysis of responder and conditions that occur, indicating that the current PT GO-JEK Indonesia has implemented SCM in the face of competition two wheels online transportation. The test data is done using Spearman rank correlation and the results of the test result that there is a relationship between the implementation of SCM in two wheels online transportation towards community economic empowerment.